Equol induces apoptosis in chemoresistant ovarian cancer cells via external pathway (Bangladesh Journal of Pharmacology, 2015)
Polyphenolic compounds present in fruits, vegetables and grains are bioactive molecules which elicit a wide range of responses both in vivo and in vitro. The aim of this study was to investigate whether the soybean isoflavone equol could induce apoptosis in ovarian cancer cells. In this study, we evaluated molecular events associated with apoptosis induced by equol and paclitaxel (PTX) in an ovarian cancer cell line SKOV-3. To assess whether growth inhibition was due to apoptosis, flow cytometry, colorimetry experiments, immunoblot analyses through measuring DNA fragmentation, the level of TRAIL,the cleavage of poly(ADP-ribose) polymerase (PARP) and the activation of caspase-3, -8 and -9 were also performed. Additional markers of apoptosis were also measured like phosphatidylserine externalization and morphological changes. In addition, glycoprotein P (P-gp) activity in SKOV-3 ovarian cancer cell line was also estimated. The experimental results showed that apoptosis was induced by extrinsic pathway triggered by certain TNF family members. Overall results suggested that equol induces apoptosis in SKOV-3 cells via a TRAIL and caspase 8-dependent pathway whereas paclitaxel leads to smaller apoptotic events when compared to that of equol.